1990
DOI: 10.1007/bf01959483
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of neonatal jaundice in low birth weight infants comparing transcutaneous, capillary and arterial bilirubin levels

Abstract: Total serum bilirubin level was assessed in a group of jaundiced low birth weight infants using three different methods. Transcutaneous bilirubinometry was compared with conventional capillary and arterial methods to investigate the over-or underestimation of neonatal jaundice. Sampling site did not influence bilirubin levels. Capillary and arterial results showed a linear correlation (r = 0.9) suggesting no influence of environmental light on peripheral bilirubin isomerization. Similar results were obtained c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…In contrast, other investigators conclude that BTc measurements cannot accurately predict BS (3). Besides these results, there are only two studies of preterm infants (1,2) that show correlations between BS and BTc similar to our ndings. In one of these studies it has been reported that BS-BTc correlations are substantially different at different postnatal days (2).…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, other investigators conclude that BTc measurements cannot accurately predict BS (3). Besides these results, there are only two studies of preterm infants (1,2) that show correlations between BS and BTc similar to our ndings. In one of these studies it has been reported that BS-BTc correlations are substantially different at different postnatal days (2).…”
Section: Discussionsupporting
confidence: 91%
“…1 The majority of earlier studies have examined the use of TcB in term and near-term neonates, [2][3][4][5][6][7] whereas studies that have been carried out in preterm neonates have yielded varying results. [8][9][10][11][12][13][14][15][16] Yasuda et al 17 reported that the correlation between TcB and TSB was similar in both preterm and term neonates. However, Namba and Kitajima 18 reported that accuracy and reliability of TcB versus TSB were diminished in neonates with birth weights <1000 g or gestational ages <28 weeks, compared with results in larger, more mature preterm neonates.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, different methods for transcutaneous bilirubin (BTc) measurement have been developed, which are faster, more convenient and painless. The most widespread transcutaneous bilirubin analyser is the Minolta AirShields Jaundice Meter (1)(2)(3)(4), but the Ingram Icterometer (4) is also often used. Several studies have shown good correlation when comparing BTc values with conventionally determined BS levels (4)(5)(6)(7).…”
mentioning
confidence: 99%
“…Several studies have shown good correlation when comparing BTc values with conventionally determined BS levels (4)(5)(6)(7). However, in most studies, full-term and healthy newborns were examined (4-7), whereas there is still a dearth of knowledge about the accuracy of BTc measurement in preterm infants (1,2). The purpose of this study was to measure serum and transcutaneous bilirubin concentrations simultaneously, using the transcutaneous measurement analyser BiliCheck 2 , to characterize more precisely the possibilities of transcutaneous bilirubinometry for recognizing clinically relevant hyperbilirubinaemia, and to detect factors in uencing the use of this method in preterm infants.…”
mentioning
confidence: 99%